2021
DOI: 10.1039/d1fo00117e
|View full text |Cite
|
Sign up to set email alerts
|

Structurally diverse triterpenes obtained from the fruits of Ziziphus jujuba Mill. as inflammation inhibitors by NF-κB signaling pathway

Abstract: Twenty-nine triterpenes were obtained from the fruits of Ziziphus jujuba Mill. by using various chromatography and the stereo-structures were confirmed by spectroscopic methods. Among them, 2α,3β,20-trihydroxylupane-28-oic acid (1) was identified...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…2-O-Trans-p-coumaroyl maslinic and 3-oxo-urs-12-en-28-oic acids had no inhibitory effect on RAW 246.7 cell activity at 5 µM and inhibited the production of NO, both of which were passed. The NF-κB signaling pathway exhibited anti-inflammatory activity by downregulating the expression of inflammatory factors [ 33 ]. Another study reported that triterpenoid saponins moderately inhibited the release of the proinflammatory cytokine TNF-αin LPS-induced RAW 246.7 macrophages [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…2-O-Trans-p-coumaroyl maslinic and 3-oxo-urs-12-en-28-oic acids had no inhibitory effect on RAW 246.7 cell activity at 5 µM and inhibited the production of NO, both of which were passed. The NF-κB signaling pathway exhibited anti-inflammatory activity by downregulating the expression of inflammatory factors [ 33 ]. Another study reported that triterpenoid saponins moderately inhibited the release of the proinflammatory cytokine TNF-αin LPS-induced RAW 246.7 macrophages [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 9 – 15 were identified by comparing the spectroscopic data with those reported in literature. The effects of compounds 1 – 15 on LPS-stimulated NO release were measured by using Griess reaction in RAW 264.7 cells 24 . Compounds 2, 3, 7 , and 12 – 15 significantly inhibited NO release at 50 µM ( Table 4 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The LPS treated RAW 264.7 cells were analyzed by Western blot using a previously reported method [24]. The protein concentrations in the supernatants and tissues were quantified with a bicinchoninic acid protein assay kit.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Indeed, altered intracellular calcium concentration can act as a crucial signal for T cell proliferation and activation [37][38][39][40]. In a previous study, ALA was shown to inhibit the nuclear factor-kappa B (NF-κB) pathway [41]. As with intracellular calcium signaling, the NF-κB pathway is associated with immune cell activity, proliferation, and differentiation, whereas the pathway proteins are engaged in activities such as epithelial cell differentiation or apoptosis [42].…”
Section: Discussionmentioning
confidence: 99%